Seasonal variation in larval density of Limnoperna fortunei (Bivalvia, Mytilidae) in the Iguaçu and Paraná rivers, in the region of Foz do Iguaçu, Paraná, Southern Brazil - Pestana,Débora (2008)
The larval density of the invasive mussel Limnoperna fortunei (Bivalvia, Mytilidae) was monitored from January 2005 to February 2006 at two points along the Paraná and the Iguaçu Rivers, near Foz do Iguaçu, PR, Brazil. The results indicated two density peaks in the Paraná River: a lower peak between March and June and a higher peak in October. In the Iguaçu River, the values were much lower, yet they also showed a peak between September and October. A reduction in the reproductive activity was observed in both the rivers between July and August. The average larval density at the collection point in the Paraná reached 948.5 larvae/m³, with a peak of 2,999.5 larvae/m³ in October. The present study represented the first quantification of the larval density of L. fortunei in the lower reaches of the Iguaçu River, downstream of the Iguaçu falls.